2018
DOI: 10.1155/2018/7465126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LI-RADS v.2017 and ESGAR Guidelines Imaging Criteria in HCC Diagnosis Using MRI with Hepatobiliary Contrast Agents

Abstract: Purpose The purpose of this study was to assess and compare diagnostic ability of LI-RADS (LR) v. 2017 and ESGAR guidelines in hepatocellular carcinoma (HCC) diagnosis using MRI with hepatobiliary contrast agents. Methods Seventy pathologically confirmed lesions in 32 patients (24 males and 8 females) who had MRI with hepatobiliary contrast done before surgery or biopsy were reviewed retrospectively. Six lesions were <10mm, 31 lesions 10-19mm, and 33 lesions ≥20mm. Two readers assessed all lesions according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In that study, five of 10 studies had only used pathology as the reference standard, which might have led to verification bias and overestimation of the probability of HCC for LR‐2 5 . In our meta‐analysis using CT/MRI LI‐RADS v2017, only one of six studies that reported the proportion of HCC for LR‐2 used pathology 13 and the other five studies used pathology and CCRS as the reference standard 12,16,18,21,24 . In addition, the definition of the LR‐2 distinctive nodule without malignant features (solid nodule <20 mm distinctive in imaging appearance compared to background nodules and with no major feature of HCC, no feature of LR‐M, and no ancillary feature of malignancy) was clearer in CT/MRI LI‐RADS v2017 4 compared to the LR‐2 cirrhosis‐associated nodule in LI‐RADS v2014, 29 which may refine the LR‐2 category so that it achieves ≤5% probability of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, five of 10 studies had only used pathology as the reference standard, which might have led to verification bias and overestimation of the probability of HCC for LR‐2 5 . In our meta‐analysis using CT/MRI LI‐RADS v2017, only one of six studies that reported the proportion of HCC for LR‐2 used pathology 13 and the other five studies used pathology and CCRS as the reference standard 12,16,18,21,24 . In addition, the definition of the LR‐2 distinctive nodule without malignant features (solid nodule <20 mm distinctive in imaging appearance compared to background nodules and with no major feature of HCC, no feature of LR‐M, and no ancillary feature of malignancy) was clearer in CT/MRI LI‐RADS v2017 4 compared to the LR‐2 cirrhosis‐associated nodule in LI‐RADS v2014, 29 which may refine the LR‐2 category so that it achieves ≤5% probability of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The LI-RADS is currently the most popular system of lesion classification in CT and MRI studies in patients with increased risk of HCC (Chernyak et al 2018 ; Kim et al 2019 ; Aslam et al 2020a ; Rosiak et al 2018b ). There are many studies showing the high specificity and sensitivity of LI-RADS for HCC reporting (Rosiak et al 2018a ; Furlan 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 18 studies comprised a total of 3386 patients (age range, 20-88 years). Three studies were prospective [17][18][19] and 14 were retrospective [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The design of another study was unclear [34].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nine studies enrolled subjects consecutively [17,[22][23][24]27,28,30,31,34]; the remaining nine studies did not describe how subjects were enrolled [18][19][20][21]25,26,29,32,33]. Seven studies used only histopathology as a reference standard [20,[26][27][28]30,33,34] and 11 studies used both histopathology and follow-up imaging as the reference standard [17][18][19][21][22][23][24][25]29,31,32]. Ten studies had fewer than three readers [18,[20][21][22][23][24][25][26]28,32], while eight studies had three or more readers [17,19,27,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%